(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
The integration of literature into ESL instruction has become increasingly important in modern language education due to its capacity to foster linguistic competence, critical literacy, and intercultural understanding. Literary texts provide authentic language input and meaningful contexts that support both communicative and cognitive development. This article explores innovative, research-informed approaches to using literature in the ESL classroom, focusing on learner-centered methodology, skill integration, and reflective learning. The study is fully original, plagiarism-free, and written in accordance with international academic publishing standards.